On Doitchinov's quietness for arbitrary quasi-uniform spaces - Kivuvu, Charly Makitu (Department of Mathematics and Applied Mathematics, 2014)
The notion of a quiet quasi-uniform space was introduced by Doitchinov in1988 when he developed an interesting completion theory for this class ofquasi-uniform spaces. At the same time Doitchinov developed a similar com-pletion theory for a class of T0-balanced quasi-pseudometric spaces.In my Masters thesis I showed that the Doitchinov completion theory forbalanced quasi-pseudometric spaces can be extended to arbitrary T0-quasi-pseudometric spaces. That completion was called the B-completion.The principal aim of this thesis is to investigate whether the Doitchinov com-pletion theory for quiet quasi-uniform space can be extended to arbitraryT0-quasi-uniform spaces. The main result in this thesis is negative and leadsus to conclude that Doitchinov's completion theory for quiet quasi-uniformspaces cannot be fully extended to arbitrary quasi-uniform spaces, becauseinvestigations due to De¶ak indicate that no suitable concept of a quiet Cauchy¯lter pair exists which could replace the quasi-pseudometric concept of a bal-anced Cauchy ¯lter pair in the quasi-uniform setting. Under these circum-stances we therefore suggest that in an arbitrary quasi-uniform space, weshould work with a nonempty subbasic family of quasi-pseudometrics and anappropriate concept of balancedness of Cauchy ¯lter pairs with respect tothat family. In this way we obtain a general theory of the B-completion fora subbasic T0-family of quasi-pseudometrics that can be applied to the studyof any quasi-uniform space.